1996
DOI: 10.1021/la9504568
|View full text |Cite
|
Sign up to set email alerts
|

Probing the Structure of Colloidal Doublets by Electrophoretic Rotation

Abstract: A doublet formed by the coagulation of two colloidal spheres rotates toward alignment with an applied electric field. The rotation rate is proportional to the difference in the zeta potentials of the two spheres and a geometric coefficient N. This coefficient can be calculated from the electrohydrodynamic equations and depends on the kinematic boundary condition imposed on the spheres. If the doublet rotates as a single rigid body, so that the surfaces of the two spheres do not move relative to one another, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
57
0

Year Published

1999
1999
2010
2010

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 37 publications
(58 citation statements)
references
References 30 publications
1
57
0
Order By: Relevance
“…This conclusion differs from the one reached by Holt and Chan (14), who considered the same doublet experiments (4,5). They argue that surface heterogeneities could result in torques of order thousands of kT "at separations comparable to the secondary DLVO minimum."…”
Section: A Case Study-torques On Doubletsmentioning
confidence: 61%
See 2 more Smart Citations
“…This conclusion differs from the one reached by Holt and Chan (14), who considered the same doublet experiments (4,5). They argue that surface heterogeneities could result in torques of order thousands of kT "at separations comparable to the secondary DLVO minimum."…”
Section: A Case Study-torques On Doubletsmentioning
confidence: 61%
“…We now consider whether our analysis of single-mode surfaces can explain the unusually strong interactions between particles in doublets observed by Velegol et al (4). They measured their particles' zeta-potentials using electrophoresis and applied a standard DLVO calculation to show that the particles in each doublet ought to sit in a secondary minimum.…”
Section: A Case Study-torques On Doubletsmentioning
confidence: 94%
See 1 more Smart Citation
“…Thus, the ζ potential is often obtained from mobility measurements and used to predict colloidal stability. However, experiments have shown that even when the mobility measurements indicate a high ζ potential, the suspension is often unstable (2,3). This and other discrepancies (e.g., in Ref.…”
Section: Introductionmentioning
confidence: 94%
“…The electrokinetic theory for this type of surface has been considered by several authors [118,119,125,126]. Anderson et al [127][128][129] have also performed experimental checks on the validity of some theoretical predictions. In the case of spherical particles, it has been demonstrated [130] that their motion depends on the first, second, and third moments of the ζ-potential distribution along the surface of the particle.…”
Section: Chemical Surface Heterogeneitymentioning
confidence: 99%